Effect of Plant Growth Regulator and Media Composition on Growth Budding Planting mukibat Cassava - sutan tarmizi lubis; nini - rahmawati; T - Irmansyah (Universitas Sumatera Utara, 2017)
The purpose of research was effect of plant growth regulator and media composition on growth budding planting cassava.This research was conducted in the screen house of Agriculture Faculty USU (± 25 m asl) from February-April 2016 using factorial group randomized design (RAK) with 3 times repitition. The first factor was source of growth regulators with four levels ie: without not giving the source of ZPT (P0), coconut water 50% (P1),shallot extract 100% (P2) and IAA 0.05% (P3) and the second factor was medium on the growth composition goat manure: top soil: rice husk with three levels of treatment are: 3: 1: 1 (M1),2: 1: 2 (M2) and 1: 1: 1 (M3).The observed parameters was the percentage of success, speed of bud, the bud length, and roots volume. The results of this research showed that the sources of growth regulators affected the speed of germination significantly. The best source of growth regulator treatment was in the level of 50% coconut water. Giving medium on the growth composition significantly affected to the speed germinate and the bud length. The best level of growing media composition is best to goat manuare: top soil: rice husk 3: 1: 1 (M1). Interactions between source of growth regulators and medium on the growth composition significantly affect the success of percentage parameter, the diameter of bud and amount leaves. Thd best level of combination treatment contained in the shallot extract 100%, coconut water 50% and growing media composition 3: 1: 1. Key words : budding, plant growth regulator, the growth composition